2019
DOI: 10.1055/s-0039-1698431
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Organic Porous Materials

Abstract: Fluorine is in many aspects unique among the elements, and its incorporation into organic molecules can dramatically change their physical and chemical properties. This minireview will survey the existing classes of fluorinated porous materials, with a particular focus on all-organic porous materials. We will highlight our work on the preparation and study of metal–organic frameworks and porous molecular crystals derived from extensively fluorinated rigid aromatic pyrazoles and tetrazoles. Where possible, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Although most reported SOFs and HOFs , up to this point were not robust enough to maintain pristine frameworks upon guest removal, their activated structures still held partial permanent porosity, which was useful for gas or liquid adsorption and separation. , In 2014, Miljanic leveraged π–π-stacking interactions to stabilize a fluorinated HOF ( Trispyrazole-1 ( L5 )), which demonstrated extremely high thermal stability, even up to 250 °C, based on variable-temperature powder X-ray diffraction (VT-PXRD) experiments . Subsequently, a series of isoreticular fluorinated HOFs with strong π–π-stacking interactions were discovered, and Trispyrazole-25 ( L11 ) demonstrated the first example of a mesoporous HOF that also exhibited high stability. , In 2016, Hisaki et al invented a series of HOFs based on C 3 -symmetric π-conjugated planar molecules ( Tp ( L12 ), T12 ( L13 ), T18 ( L14 ), and Ex ( L17 )) . Though π–π-stackings interactions were observed in the as-synthesized HOFs, the desolvated frameworks show obvious phase changes in VT-PXRD experiments, indicating that not all kinds of π–π stackings can effectively increase the HOF stability.…”
Section: History Of Hofsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most reported SOFs and HOFs , up to this point were not robust enough to maintain pristine frameworks upon guest removal, their activated structures still held partial permanent porosity, which was useful for gas or liquid adsorption and separation. , In 2014, Miljanic leveraged π–π-stacking interactions to stabilize a fluorinated HOF ( Trispyrazole-1 ( L5 )), which demonstrated extremely high thermal stability, even up to 250 °C, based on variable-temperature powder X-ray diffraction (VT-PXRD) experiments . Subsequently, a series of isoreticular fluorinated HOFs with strong π–π-stacking interactions were discovered, and Trispyrazole-25 ( L11 ) demonstrated the first example of a mesoporous HOF that also exhibited high stability. , In 2016, Hisaki et al invented a series of HOFs based on C 3 -symmetric π-conjugated planar molecules ( Tp ( L12 ), T12 ( L13 ), T18 ( L14 ), and Ex ( L17 )) . Though π–π-stackings interactions were observed in the as-synthesized HOFs, the desolvated frameworks show obvious phase changes in VT-PXRD experiments, indicating that not all kinds of π–π stackings can effectively increase the HOF stability.…”
Section: History Of Hofsmentioning
confidence: 99%
“…In addition to remarkable stability, this porous structure also shows high fluorophilicity and can serve as a potential adsorbent for hydrocarbons and their halogenated derivatives, which are potent greenhouse gases. Miljanic and co-workers further prepared a series of derivatives of the original building blocks by varying their geometry, length, and propensity for H-bonding and stacking interactions to ascertain the exact role of each molecular feature in the formation of porous solid-state structures . For example, Trispyrazole-1 ( L5 ) and Trispyrazole-16 ( L39 ) are isostructural and exhibit similar solid-state absorption and fluorescence emission spectra; however, the rotation of tetrafluorinated rings in Trispyrazole-16 ( L39 ) is relatively less hindered due to the absence of hydrogen atoms on the central ring of its tecton.…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…This analysis shows that the destabilizing Pauli steric term strongly influences these compounds′ catalytic activity, but results are principally favored in Pd‐CFA‐1 by ΔΔΔE Pauli =−7.1 kcal/mol. One might envision that the smaller size of the fluorine atoms will allow to accommodate it easily into the pore wall of the MOF structure, where also it has been demonstrated that fluorine atoms into the pore of the framework serve as stabilizing agents [34] . The latter could be one reason why the substrate‘s interaction is more favored than non‐fluoridated species.…”
Section: Resultsmentioning
confidence: 99%
“…One might envision that the smaller size of the fluorine atoms will allow to accommodate it easily into the pore wall of the MOF structure, where also it has been demonstrated that fluorine atoms into the pore of the framework serve as stabilizing agents. [34] The latter could be one reason why the substrate's interaction is more favored than non-fluoridated species. In addition, attractive electrostatic (ΔΔΔE elstat ) and charge transfer (ΔΔΔE ct ) terms in the fluorinated MOF deriva-tive compensate the steric effects reducing the energy barrier compared with the ground state in the π-complex more than they reduce this difference in energy for its nonfluorinated counterpart.…”
Section: Ligand Effects On the Activitymentioning
confidence: 99%
“…2 Fluorination of functional organic molecules and materials has often been used to modulate their physical and chemical characteristics. 3 Partial fluorination of the TPE structural motif was reported to increase the fluorescence quantum yields in crystals 4a,b in addition to simplifying the separation of isomers on account of strong dipole-dipole intermolecular interactions. 4c Our work on fluorinated aromatic pyrazoles 5 suggested that the intra-and intermolecular interactions of fluorinated aromatic rings influence the molecules' AIE activity 6 and allow emission color switching in aggregates and the solid state.…”
mentioning
confidence: 99%